(3GdEYLGR hGdEjLGRs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3eMjj GdOjf eMeO s)
(3ChdgG (B:s
(3ef ahbj Ch eKdj, hdSJ CbOQ Ydi GdEfJbGe efg hcGf jbhd aj GdfSGA(B: (3jZdHf GdcQGe hjZdHgf GddFGe, hjbhd(B: (3GdJSdW Ydi GdeeGdjc ef dDe GdbOQI s
(3BNQgG (B:s
(3ce hGdO jMQe ChdGOg hNjQg jMXi Hg GdCHYO cGdYjf dG JHUQ eG MhdgG hdMXgG jOQc eG jHYO Je cJGH GdEYLGR hGdEjLGR s
(3JNJda Yf GdfSNI GdSGHbI cKjQkGs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B35 s
Keywords: (3GdCOHs